Measuring park visitation vulnerability to climate extremes in U.S. Rockies National Parks tourism. Issue 2 (15th March 2018) - Jedd, Theresa M.; Hayes, Michael J.; Carrillo, Carlos M.; Haigh, Tonya; Chizinski, Christopher J.; Swigart, John
ABSTRACT: Changes in temperature and precipitation can affect tourist experiences. This study examines how summer park visitation has changed in response to temperature and precipitation extremes. The study goals were two-fold. The first is to introduce a framework and the second is to test it in a pilot region with four mountainous National Parks. The framework is designed to compare the vulnerability of seasonal park visitation to shifts in a combined indicator of temperature and precipitation. It uniquely considers needed measurements, and the data required to conduct an analysis. The second goal is to test it in four destinations in the U.S. Northern Rockies, including Glacier, Yellowstone, Grand Teton, and Rocky Mountain National Parks. The preliminary test reveals outlier cases of visitation under wet and dry extremes. The analysis connects time series climate and visitation data for the peak summer season from 1991–2012. Outlier analysis illustrates more change in extremely dry conditions, with four out of the six dry-year outliers resulting in a visitation decline. Whether this decline in park tourism is attributable to climate features, economic factors, or conscious management decisions, these drops have significant economic impacts: estimates of changes in visitor spending during dry years are between roughly 9 and 90 million USD. These differences may be connected to the popular activities in each park, and the extent they are dependent on weather conditions. This framework can be used to test the relationship between climate and tourism visitation in other regions, in various seasons and time frames. The work may inform the tourist sector in adjusting and planning for a range of conditions. We discuss opportunities and conclude with additional needs for understanding the mechanisms behind risk in mountain park tourism under climate extremes.